1996
DOI: 10.1007/bf02649778
|View full text |Cite
|
Sign up to set email alerts
|

Convection during thermally unstable solidification of Pb-Sn in a magnetic field

Abstract: Convection and macrosegregation in directionally solidified hypoeutectic Pb-38 wt pct Sn and hypereutectic Pb-64.5 wt pct Sn have been examined during upward and downward growth. Temperature fluctuations are observed along the length of the melt column during downward growth. With increasing Rayleigh number, these fluctuations change from none, to cyclic, to time periodic having multiple harmonics, and finally to random. At the higher convective driving force of 350 K temperature inversion, the transverse magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…rosegregation, even when it is strong enough to suppress channel flow. However, Song et al [27] also found that,…”
Section: Effects Of An Applied Magneticmentioning
confidence: 96%
“…rosegregation, even when it is strong enough to suppress channel flow. However, Song et al [27] also found that,…”
Section: Effects Of An Applied Magneticmentioning
confidence: 96%
“…The buoyancy induced melt flow and transport of solid that occurs during solidification generates compositional and structural nonuniformities at the macroscopic level [3,4]. It is the goal of models, such as that by Beckermann and Wang [5], to predict such compositional and structural nonuniformities in an attempt to minimize their negative effect on the final properties of a casting.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have resulted in the determination of the interfacial drag between equiaxed dendrites and the melt over a wide range of solid volume fractions. A study that illustrated the effects of convection was done by Hellawell et al [15] using an aqueous solution of NH 4 Cl. In this study [15] channel plume flow and convective transport of solid fragments were observed causing macrosegregation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10(a) is the superposed diagram of the C distribution, g S contours, and fluid flow vectors. Figure 10(b) is T vs g S relationships at the element number (I = 20, K = 58; I and K are the element numbers in X and Z directions, respectively) marked by a white diamond and at element (20,56), which is 2 elements below element (20, 58) with negative segregation. Figure 10(c) shows how the C concentration and g S at the element (20, 58) vary along with the segregation parameter** as time proceeds.…”
Section: A Channel Segregation In Large Steel Ingotmentioning
confidence: 98%
“…However, most of them are concerned only with bulk liquid zone or with negligible mushy zone. With respect to the DS of alloys with an extensive mushy zone, only limited research has been devoted to study the effects of the magnetic field: Tewari et al [19] and Song et al [20] have carried out the DS experiments on Pb-Sn alloys to investigate the effects of magnetic field (maximum 0.45 Tesla) on the mushy zone morphology and macrosegregation. These authors stated, as far as the macrosegregation is concerned, that the magnetic field had no influence on the formation of it (freckle).…”
Section: Introductionmentioning
confidence: 99%